BLOCKCHAIN AND CRYPTOCURRENCY TECHNOLOGIES: A NEW STAGE OF THE MODERN ECONOMY - Abdusalomova Istoraxon Ilhom qizi; Abdumo'minova Farangiz Ilyos qizi (Ecominds Press, 2025)
The article analyzes the essence of blockchain and cryptocurrency technologies, their principle of operation, practical application and role in the modern economy. The technological advantages and security systems of cryptocurrencies, as well as the prospects for the digital economy developing on their basis, are considered.
Keywords: Blockchain, cryptocurrency, digital economy, Bitcoin, Ethereum, smart contract, decentralization.